(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
Sommario: 1. La perfezione del creato come epifania di Dio - 2. Lo sguardo laico e quello della Chiesa di fronte al disordine ecologico - 3. La creazione come atto di affidamento all’uomo - 4. Ineludibili implicazioni etico-giuridiche del munus di custodia. Dall’aversio alla conversio: rieducare alla responsabilità solidale - 5. Conclusioni. Aversio to Deo: the origin of ecological reflection in the papal magisterium from Leo XIII to Francis ABSTRACT: This study aims to retrace some fundamental stages of the Social Doctrine of the Church in relation to the emergence of sensitivity on the issues of the environmental question which translates into the magisterium of the Popes, from Leo XIII onwards, with the ecological question understood in a broader sense. The key point is represented by the identification of man’s responsibility for his aversion to Deo and the custody mandate that was entrusted to him by the creator. The solution can be found in the recovery of respect for the natural order and solidarity between creatures in the frame of human ecology.